Rancangan UI/UX Aplikasi Pite Tenun Dengan Edukasi Budaya Menggunakan Metode Design Thinking - Wilitama Tantosa; Lalu A Syamsul Irfan Akbar; Cipta Ramadhani (Bulletin of Computer Science Research, 2025)
Woven fabric is an Indonesian cultural wealth that can be found in various regions, one of which is in Sukarara Village, Lombok. Sukarara woven fabric is known as "songket fabric" with strong religious and cultural values so that it becomes a preserved heritage and the main source of livelihood for the village community. However, currently many outsiders are taking advantage by making weaving motifs and then printed and sold at very cheap prices. So that it causes a decline in the existence of cultural values in woven fabrics. The purpose of the study is to produce a UI/UX design design of the Pite Tenun application with Cultural Education in Sukarara Village and to get measurable results from the design results of prospective users using the System Usability Scale. This app is made with an attractive design with UI/UX that is tailored to your needs. Therefore, the Pite Tenun application is designed to be able to carry out an informative process of selling woven fabrics from the materials used and more accurate product details, in addition to the addition of the story of Sukarara Village Weaving and its history is expected to be a trusted cultural education and can increase the existence of cultural values in it. The results of the research obtained show that the UI/UX design of the Pite Weaving application with Cultural Education in Sukarara Village was successfully implemented. The results obtained have been measured from the design of prospective users using the System Usability Scale with a score of 2197.5 and the average total number of respondent scores is 73.25%. The results are categorized as excellence (grade B) based on SUS scores.